Beta-hydroxybutyrate (BHB) elicits concentration-dependent anti-inflammatory effects on microglial cells which are reversible by blocking its monocarboxylate (MCT) importer - Chase Garcia; Ariana Banerjee; Claire Montgomery; Lauren Adcock; Izumi Maezawa; Jon Ramsey; Ana Cristina G. Grodzki; Kyoungmi Kim; Gino Cortopassi (Frontiers in Aging, 2025)
IntroductionThe ketogenic diet (KD) increases mouse lifespan and health span, and improves late-life memory. This raises the question regarding the mechanism behind this effect. In mice on a KD, blood beta-hydroxybutyrate (BHB) levels uniquely rise higher than those of mice on a control diet (CD). BHB is therefore considered a key signaling and metabolic mediator of KD’s effects and benefits. BHB crossed the blood–brain barrier and rescued memory, improved cognitive function, and increased neuronal plasticity in two different mouse models of Alzheimer’s disease (PS1/APP and 5XFAD). At the cellular level, microglia are thought to play a critical role in the physiologic basis of memory due to their important role in synaptic development, plasticity, and connectivity. Conversely, microglial dysfunction and inflammation are connected to cognitive decline and neurodegenerative diseases. Because of this, one explanatory hypothesis for these positive therapeutic observations in mice is that the KD and BHB drive memory and longevity benefits through their anti-inflammatory actions on microglia.MethodWe investigated the concentration dependence of BHB’s antiinflammatory effects in BV2 microglial cells. We focused on 1.5 mM BHB, which reflects blood levels in mice and humans on a KD.ResultsAt this concentration, BHB significantly and concentration-dependently decreased the following: 1) inflammatory cytokine expression (IL-6, TNF-α, and IL-1β), 2) inflammatory morphological changes, and 3) activation of p-ERK and p-p38MAPK, which are key pathways involved in microglial inflammation. We show, for the first time, that the expression of Alzheimer’s risk gene TREM2 is modified by dietarily-achievable 1.5 mM BHB. BHB’s anti-inflammatory, morphological, biochemical, and TREM2 effects were blocked by a monocarboxylate transporter (MCT) inhibitor, supporting the idea that BHB must enter microglia to elicit some of its anti-inflammatory effects.DiscussionThese results support the hypothesis that blood BHB levels achievable on a KD elicit significant concentration-dependent anti-inflammatory effects in microglia. Increasing BHB concentration through sustained KD, or BHB supplements, may lower microglial inflammatory tone and provide benefits in age-related memory loss.